(untitled) (Journal of Environmental Microbiology and Toxicology, 2022)
Availability of potable water is important for healthy living. Domestic water is usually supplied to homes through private wells, boreholes and public water companies. This study aimed at evaluating bacteria from private well water samples which serves as a major water source in the study area (Akungba-Akoko). Samples were subjected to total bacterial and coliform counts using nutrient agar and eosin-methylene blue (EMB) respectively. All isolates were identified based on their morphological and biochemical characteristics. This was followed by antibiotics sensitivity test (AST). The result showed that total bacterial count ranged from 4.0 ×103 CFU/mL to 22.5 × 103 CFU/mL while total coliform count ranged from 1.0 × 100 CFU/mL to 7 × 100 CFU/mL. Gram positive bacteria belonging to the following genera; Bacillus, Corynebacterium, Enterococcus, Micrococcus, and Staphylococcus were obtained, while Gram negative bacteria include; Alcaligenes, Campylobacter, Citrobacter, Enterobacter, Escherichia, Klebsiella, Pseudomonas and Salmonella. Enterobacter and Pseudomonas had the highest percentages of occurrence of 15%. P. pseudo-mallei had the highest sensitivity to ofloxacin (23 mm), followed by P. fluorescens (22 mm) and C. freundii (22 mm) while B. subtilis was susceptible to ciprofloxacin, erythromycin, levofloxacin. The result showed high level of bacterial contamination in all samples tested. The coliform count of all water samples exceeded the recommended level of zero. Hence, there is the need for proper wells water maintenance, control and improve hygienic practices by the households and individuals to help solve the risk of disease outbreak.